Implementasi Jenis Khat Naskhi dalam Pembelajaran Bahasa Arab - Nurul Huda (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2017)
This paper aims to obtain a description of various types of Arabic calligraphy, to find out the extent to which Naskhi type calligraphy is used in basic Arabic learning and to know the factors that support the optimization of the use of Naskhi khat in basic Arabic learning. This type of research is field research with a qualitative approach. Data analysis uses descriptive analytic. Based on the analysis, it can be concluded that Arabic with calligraphy is an integrated one even in a learning model, both are interrelated and supportive. The relationship can be seen through several aspects; aspects of history, practical aspects, aspects of form, aspects of character and aspects of psychology. The factors that support the use of Khat Naskhi are the factors of teachers and students in line with learning methods and media. While the analysis of the role of the use of Khat Naskhi in basic Arabic language learning is: 1. Khat Naskhi helps the process of learning Arabic. 2. Khat Naskhi helps writing skills in basic Arabic. 3. Khat Naskhi helps reading skills in basic Arabic, and 4. Khat Naskhi also plays a role in student learning.